Hubungan Pengetahuan Tentang Tingkat Kecukupan Gizi Dan Perilaku Pemberian Makan Ibu Dengan Kejadian Stunting Pada Balita Di Medan Belawan - Sitorus, Fransiska Febiola; Aulia, Dwana Mutiara; Angraini, Fifi; Putri, Andini Aisyah; Chairunnisa, Putri; Haryana, Nila Reswari (Peneliti.net, 2025)
Stunting is one of the worrying nutritional problems and is an important concern in Indonesia. The reason is that many people still think that stunting is not a serious problem, only a condition of the child's height is lacking. Based on the results of the SSGI, the prevalence of stunting in North Sumatra in 2022 was 21.1%. This study aims to examine the relationship between knowledge of nutritional adequacy levels and maternal feeding behavior with the incidence of stunting in toddlers. The research method used is quantitative research with a Cross Sectional approach. The population in this study were mothers who had toddlers in the Posyandu area of ​​Medan Belawan District, totaling 80 mothers of toddlers. The number of samples was 30 respondents. The sampling technique used purposive sampling. This study was conducted from June to July 2024. The data collection technique was carried out by interview using a questionnaire. The descriptive data analysis technique used the Spearman rank test. Based on the results of the test using the Spearman rank, it is known that in the knowledge variable, 66.7% of mothers had poor knowledge (20 people), 30% of mothers had sufficient knowledge (9 people), and the remaining 3.3% had good knowledge (1 person). In the variable of eating parenting patterns, 40% (12 people) of mothers had parenting pattern scores in quartile 1, 23.3% (7 people) of mothers had parenting pattern scores in quartile 3, 20% (6 people) of mothers had parenting pattern scores in quartile 4, and the remaining 16.7% (5 people) of mothers had parenting pattern scores in quartile 2. And in the variable of stunting incidence, 56.7% (17 people) of toddlers experienced stunting and the remaining 43.3% (13 people) of toddlers did not experience stunting. The results of the study showed no significant relationship between the level of maternal knowledge and the nutritional status of toddlers p = 0.534> (0.05), and between eating parenting patterns and the nutritional status of toddlers p = 0.727> (0.05). However, there are other factors that allow stunting to occur in toddlers, namely from the socio-culture of parents such as parental occupation, parental education, and parental income.